2003
DOI: 10.1073/pnas.2332326100
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by environmental stresses and amphotericin B inCandida albicans

Abstract: New antifungal agents are urgently required to combat lifethreatening infections caused by opportunistic fungal pathogens like Candida albicans. The manipulation of endogenous fungal programmed cell death responses could provide a basis for future therapies. Here we assess the physiology of death in C. albicans in response to environmental stresses (acetic acid and hydrogen peroxide) and an antifungal agent (amphotericin B). Exposure of C. albicans to 40 -60 mM acetic acid, 5-10 mM hydrogen peroxide, or 4 -8 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
351
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(384 citation statements)
references
References 51 publications
26
351
1
1
Order By: Relevance
“…This activation would trigger self-protection, since the absence of the activity of these kinases in the macrophage leads to apoptosis in the presence of GSNO (Callsen & Brune, 1999). Since C. albicans undergoes apoptosis in the presence of oxidative stress (Phillips et al, 2003), Mkc1p phosphorylation could avoid apoptosis in the presence of NO radicals generated by macrophages. This activation could contribute to the survival rate of 80 % of C. albicans after macrophage endocytosis (Ibata-Ombetta et al, 2001), a process that increases the expression of ROS detoxifying genes and DNAdamage repair genes (Lorenz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This activation would trigger self-protection, since the absence of the activity of these kinases in the macrophage leads to apoptosis in the presence of GSNO (Callsen & Brune, 1999). Since C. albicans undergoes apoptosis in the presence of oxidative stress (Phillips et al, 2003), Mkc1p phosphorylation could avoid apoptosis in the presence of NO radicals generated by macrophages. This activation could contribute to the survival rate of 80 % of C. albicans after macrophage endocytosis (Ibata-Ombetta et al, 2001), a process that increases the expression of ROS detoxifying genes and DNAdamage repair genes (Lorenz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The features of apoptosis include externalization of phosphatidylserine, chromatin condensation, accumulation of ROS, DNA degradation, and caspase activation. 15,23,24 Candida spp undergoing apoptosis exhibit biochemical hallmarks similar to those of mammalian apoptosis in response to diverse stimuli, 15,25 in which mitochondria play a pivotal role in controlling both caspase-dependent and caspase-independent cell death pathways. ROS accumulation and mitochondrial dysfunction signal the onset of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 Recent studies have demonstrated that planktonic and sessile C. albicans cells undergo apoptosis when exposed to amphotericin B and caspofungin, via activation of cysteine-dependent, aspartate-specific proteases (caspases). 13,15,16 However, to our knowledge, no study has assessed in a biofilm environment, the mechanisms of cell death in Candida albicans and Candida parapsilosis induced by the echinocandin micafungin (MICA), an echinocandin that inhibits (1, 3)-b-D glucan synthesis in the cell wall. Elucidation of novel targets or mechanisms for enhancing the activity of current antifungals against Candida biofilms is critical for improving outcomes of biofilm associated Candida infection.…”
Section: Introductionmentioning
confidence: 99%
“…For example excessive Ras signalling has also been shown to lead to apoptosis in the fungal pathogen Candida albicans. 80,81 The prevention of aggregate formation by addition of the actin monomer sequestering drug Lat-A was sufficient to prevent apoptosis. 82 This strengthens the proposal that the formation of stable F-actin structures, or aggregates, exerts an effect as the initiating factor within this apoptotic pathway.…”
Section: Actin Environmental Sensing and Apoptosis In Yeastsmentioning
confidence: 99%